Constituent Composition of Harmattan Dust and its Influence on Properties of Fadama Soils in Semi-Arid Region, North East Nigeria - Kundiri, A. M.; Alhassan, A. B.; Audu, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
A study of the soils of the fadama around Gashua was carried out to assess the contribution of harmattan dust deposition on their genesis and characteristics. The surface horizons have medium coarse prismatic structure or strongly developed coarse subangular or angular blocky which becomes coarse prismatic with depth. The surface horizons typically have loam to sandy loam textures and low bulk density values (<1.17). The annual addition of the harmattan dust has the potential of improving the nutrient contents of fadama soils. This study shows that harmattan dust is an important soil-forming factor in fadama soil pedogenesis and represents a significant natural process in the fluvial ecosystems. The clay minerals of dust and soil were similar, being dominated by kaolinite and illite, with smaller amounts of vermiculite.  It is concluded that harmattan dust contributes significantly to the fertility of fadama soils.